Cerebral Small Vessel Disease in Elderly Patients With Vestibular Neuritis - Oussoren, Fieke K.; Poulsen, Louise N. F.; Kardux, Joost J.; Schermer, Tjard R.; Bruintjes, Tjasse D.; van Leeuwen, Roeland B. (Frontiers in Neurology, 2022)
Background Acute audiovestibular loss is a neurotologic emergency of which the etiology is frequently unknown. In vestibular neuritis a viral genesis is expected, although there is insufficient evidence to support viruses as the only possible etiological factor. In sudden deafness, a vascular etiology has been proposed in elderly patients, since cardiovascular risk factors are more frequently present and a higher risk of developing a stroke was seen compared to the general population. So far, very little research has been carried out on vascular involvement in elderly patients with vestibular neuritis. Cardiovascular risk factors have a positive correlation with cerebral small vessel disease, visible as white matter hyperintensities, brain infarctions, microbleeds and lacunes on MRI. The presence of these characteristics indicate a higher risk of developing a stroke. Aim We investigated whether elderly patients with vestibular neuritis have a higher prevalence of vascular lesions on MRI compared to a control cohort. Materials and Methods Patients of 50-years and older, diagnosed with vestibular neuritis in a multidisciplinary tertiary referral hospital, were retrospectively reviewed and compared to a control cohort. The primary outcome was the difference in cerebral small vessel disease on MRI imaging, which was assessed by the number of white matter hyperintensities using the ordinal Fazekas scale. Secondary outcomes were the presence of brain infarctions on MRI and the difference in cardiovascular risk factors. Results Patients with vestibular neuritis (N=101) had a 1.6 higher odds of receiving a higher Fazekas score than the control cohort (N=203) (p=0.048), there was no difference in presence of brain infarctions (p=1.0). Hyperlipidemia and atrial fibrillation were more common in patients experiencing vestibular neuritis Conclusion: We found a positive correlation of white matter hyperintensities and VN which suggests a vascular involvement in the pathophysiology of vestibular neuritis in elderly patients. Further prospective research is necessary to confirm this correlation.